Modelling and Simulation of the Energy Efficiency of Heterogeneous Integrated Systems at System Level - Glock, Stefan; Fischer, Georg; Weigel, Robert; Ußmüller, Thomas (ITG-Fb. 239: Analog 2013, 2013)
In recent years, the minimization of the power dissipation of integrated heterogeneous systems has become one of the most important design goals. At specification level, at which not all architectural decisions have been taken, exists the highest potential to minimize the power dissipation of the whole system. However, the high complexity of modern het-erogeneous systems complicates the estimation of the power dissipation. Especially the analysis of the power dissipa-tion beyond subsystems is challenging because it necessitates the joint simulation of analogue and digital subsystems. In this context, the question of the right abstraction level for the joint evaluation is demanding because analogue system design follows the bottom-up paradigm, whereas digital system design follows the top-down paradigm. This paper pro-poses a new methodology to model the power dissipation and energy efficiency of complex heterogeneous systems at specification level. The method is based on the hardware description language SystemC. The methodology enables ear-ly power estimation of complete heterogeneous systems. The performance of the modelling approach is shown exem-plarily on an RF-receiver of a mobile radio platform. Those platforms are both battery driven and portable. Therefore, low power consumption is of utmost importance with respect to the later success of the product.
elib2cris::1512001600,glock2013a